Proteoglycans as Mediators of Cancer Tissue Mechanics - Barkovskaya, Anna; Buffone, Alexander; Žídek, Martin; Weaver, Valerie M. (Frontiers in Cell and Developmental Biology, 2020)
Proteoglycans are a diverse group of molecules which are characterized by a central protein backbone that is decorated with a variety of linear sulfated glycosaminoglycan side chains. Proteoglycans contribute significantly to the biochemical and mechanical properties of the interstitial extracellular matrix where they modulate cellular behavior by engaging transmembrane receptors. Proteoglycans also comprise a major component of the cellular glycocalyx to influence transmembrane receptor structure/function and mechanosignaling. Through their ability to initiate biochemical and mechanosignaling in cells, proteoglycans elicit profound effects on proliferation, adhesion and migration. Pathologies including cancer and cardiovascular disease are characterized by perturbed expression of proteoglycans where they compromise cell and tissue behavior by stiffening the extracellular matrix and increasing the bulkiness of the glycocalyx. Increasing evidence indicates that a bulky glycocalyx and proteoglycan-enriched extracellular matrix promote malignant transformation, increase cancer aggression and alter anti-tumor therapy response. In this review, we focus on the contribution of proteoglycans to mechanobiology in the context of normal and transformed tissues. We discuss the significance of proteoglycans for therapy response, and the current experimental strategies that target proteoglycans to sensitize cancer cells to treatment.